2006
DOI: 10.1002/pon.1083
|View full text |Cite
|
Sign up to set email alerts
|

The impact of parental cancer on the adolescent: an analysis of the literature

Abstract: Research has revealed the impact of the diagnosis of cancer on an individual, their spouse, and their family. One dimension that has received little attention is the impact of the cancer diagnosis on the patient's adolescent. This article offers an analysis of descriptive studies, intervention studies, and databased book chapters, published between 1966 and 2006, that examined the impact of parental cancer on the adolescent. The results of 45 studies and three databased book chapters are organized around four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
138
2
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(154 citation statements)
references
References 47 publications
3
138
2
11
Order By: Relevance
“…However, despite a wide-ranging literature search supported by an information specialist, we found little research on the subsequent process -when patients tell family members/friends their bad news. A few studies have explored communicating a parental cancer diagnosis to children and adolescents [13,14], particularly in relation to breast cancer [15][16][17] and genetic risk for cancer [18][19][20]. However there is a dearth of literature relating how patients relay bad news of a cancer diagnosis to adult significant others, what we refer to here as sharing bad news.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite a wide-ranging literature search supported by an information specialist, we found little research on the subsequent process -when patients tell family members/friends their bad news. A few studies have explored communicating a parental cancer diagnosis to children and adolescents [13,14], particularly in relation to breast cancer [15][16][17] and genetic risk for cancer [18][19][20]. However there is a dearth of literature relating how patients relay bad news of a cancer diagnosis to adult significant others, what we refer to here as sharing bad news.…”
Section: Introductionmentioning
confidence: 99%
“…However, children of patients with cancer frequently change roles within their family as well, absorbing more responsibility while one parent cares for the ill parent (4,16). The literature shows that both children and adolescents have increased personal responsibilities, resulting in a decrease in social activity and subsequent loss of childhood at a time when peer groups are essential for social development (4,10,14,17).…”
Section: Role Changesmentioning
confidence: 99%
“…The psychological and behavioral changes observed in children and adolescents can be categorized as internalizing problems, affecting the mental, cognitive, or emotional functioning and externalizing problems, which include outward directed aggression or disruptions in a social or school setting (7,13,16). Preschool children have an increased difficulty in separating from their mothers, while children of all ages display a wide range of emotions including anger, anxiety, confusion, sadness, uncertainty, and fear (3,7,11).…”
Section: Emotional Problemsmentioning
confidence: 99%
“…A cross-sectional study from Canada found that breast cancer survivors with children experience higher levels of fear of cancer recurrence and report more problems in intimacy many years after diagnosis 146 . It seems that parenting adolescent children can be particularly challenging and emotionally stressful for a young woman with breast cancer 147 .…”
Section: Psychological and Social Burden Of Breast Cancer In Young Sumentioning
confidence: 99%